Work-Related Burnout, Compassion Fatigue, and Nurse Intention to Leave the Profession During COVID-19 - Christianson, Jacqueline; Johnson, Norah; Nelson, Amanda; Singh, Maharaj (Nurse leader, 2023)
The purpose of this mixed-method study was to understand the relationships between work-related burnout (WRB), compassion fatigue (CF), and intention to leave the nursing profession. The Job Demands-Resources model was used to predict intention to leave as a function of WRB, CF, and caring for COVID-19 patients in a sample of 1299 US nurses. Greater WRB and CF scores were associated with intention to leave the profession. Contrary to prior research, working with COVID-19 patients was associated with greater intention to stay in nursing. Personal finances may represent the rationale for nurses to choose to stay nurses despite burnout.